Essence and main directions of production diversification at the food industry enterprises. - Suyunov J (Universitas Muhammadiyah Sidoarjo, 2019)
This paper makes analyses of the research on different industrial enterprises. In this case, essence and main directions of production diversification at the food industry enterprises were discussed both methodologically and practically.